‘KORIDOR KARANGWANGI’ SEBAGAI STRATEGI PENGEMBANGAN WISATA KEKINIAN YANG BERBASIS BUDAYA KOTA CIREBON - Yoyon Indrayana (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2020)
The city of Cirebon has a lot of potential for both tangible and intangible historical cultural heritages, so it is only right that the Cirebon city government makes all the riches of historical cultural heritage as a potential for future tourism. A comprehensive and integrated effort is needed in developing the city of Cirebon as a city for cultural tourism by involving many stakeholders, both from the government, DPRD, private sector, community and also actors of art and culture, so that Cirebon City can become a leading cultural tourism city. The large number of cultural potentials it has compared to other areas in West Java Province, makes Cirebon City has a very big opportunity to become a city for cultural tourism that is superior to others. With so many cultural heritages from various historical periods that are owned, there is no doubt that the superiority of cultural heritage values ​​in the city of Cirebon has a very high value and must be preserved and maintained as part of the effort to preserve the nation's culture. In order to further increase tourism in the city of Cirebon, contemporary tourist destinations need to be developed to serve the desires and tastes of tourists. The Karangwangi Corridor can be a strategy for developing cultural tourism that can be done. Several attempts to make it happen, such as; physical arrangement of roads that are good and beautiful, engineering traffic so they don't get jammed, arrangement of pedestrians so that pedestrians feel comfortable, arrangement of green open spaces so that the area becomes shady, arrangement of street furniture that adds to the aesthetics of the road, arrangement of city lights as lighting, arrangement billboards to be orderly and beautiful, and so on.